PENGARUH CURRENT RATIO, PERIODE PENAGIHAN PIUTANG DAN RETURN ON ASET TERHADAP NET PROFIT MARGIN PADA PT AUTO PARTS CENTER BALIKPAPAN - handayani, fice (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2018)
The research expected to find the influences of current asset, the collection period of receivable add return on asset against net profit margin on PT.Auto Parts Center Balikpapan. This research uses sondary data. The sample uses 11 years by collecting financial statements data from 2005-2015. The method uses to analyze the relation between independent variable with dependent variables is multiple linear regression method and assumption test.          The result of the discussion shows that simultaneously. Independent variables ;Current Ratio, the collection period of receivables and return on asset (ROA) by f test affects the net profit margin.This the result of partial test by t test , return on asset variable has an effect on net profot margin.   Key Words : NPM, Current Ratio, The collection period of receivables and ROA